Justification of antiadhesive components choice for the composition of effervescent tablets with thick extract of betula verrucosa leaves - O. O. Chumak; Ye. A. Bezrukavyi (Zaporozhye State Medical University, 2018)
Abstract Urolithiasis and inflammatory diseases of the urinary system are of great importance in recent times. Only urolithiasis affects about 15 % of the population. Therefore, the development of new domestic drugs for the treatment of urinary system disorders is an urgent task. In the pharmaceutical market of Ukraine, there are medicinal products of plant origin that exhibit antispasmodic, antiseptic, anti-inflammatory, diuretic effects, as well as dissolve concrements and eliminate them from urine. Aim of the work. To determine the optimal composition of antiadhesive components for the production of effervescent tablets with a thick extract of silver birch leaves. Materials and methods. During the experiment, the effects of macrogol 6000, macrogol 4000, glycine and fumaric acid on the technological characteristics of the model granulates and the resulting tablets were investigated. In the experiments, modern equipment and techniques were used to study tablets ejection force, granules fluidity, strength of tablets, disintegration of tablets. Results. Macrogols of 4000 and 6000 showed the best results in all studies. With satisfactory flow rates, they showed a high anti-adhesive ability and the resulting tablets had the highest rates of crushing resistance. Macrogol 4000 has the most optimal anti-adhesive properties, while the most intense reduction in the pressure of pushing tablets from the matrix is observed at its content under 4 %. Macrogol 6000 has satisfactory lubricating properties, but at a concentration of 6 %. Thus, based on the performed studies, it has been found that for the production of effervescent tablets with a thick extract of silver birch leaves it is advisable to use the macrogol 4000 (or macrogol 6000) as the antiadhesive component. Conclusions. Hydrophilic lubricants (macrogols 4000 and 6000, glycine, fumaric acid) were used to determine the optimal composition of anti-adhesive excipients to produce effervescent tablets with a thick extract of silver birch leaves, among which the best results for all were shown by macrogols 4000 and 6000. According to the results of the research, as the antiadhesive component for the preparation of tablets with thick extract of silver birch leaves, macrogol 4000 was selected which showed high antiadhesive ability and the obtained tablets had the highest indices for resistance to crushing, while the most intense reduction of the pressure of pushing out tablets from the matrix was observed at macrogol 4000 concentration up to 4 % in tablet mass.